2013
DOI: 10.1530/rep-13-0058
|View full text |Cite
|
Sign up to set email alerts
|

Epididymosomes, prostasomes, and liposomes: their roles in mammalian male reproductive physiology

Abstract: Mammalian spermatozoa are unique cells in many ways, and the acquisition of their main function, i.e. fertilization capacity, is a multistep process starting in the male gonad and ending near the female egg for the few cells reaching this point. Owing to the unique character of this cell, the molecular pathways necessary to achieve its maturation also show some specific characteristics. One of the most striking specificities of the spermatozoon is that its DNA is highly compacted after the replacement of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
226
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(238 citation statements)
references
References 122 publications
5
226
0
7
Order By: Relevance
“…Gestational or early life exposures likely reprogram primordial germ cells in the embryonic gonadal ridge or immature postnatal testis, and insults later in life may instead impact germ cells further along in spermatogenesis (64). Once sperm are fully mature, they are stored in the epididymis where epigenetic marks are thought to be largely impervious to change or to the environment (65), although limited evidence of intercellular communication between mature sperm and the epididymal epithelial cells suggests that small noncoding RNA populations in mature sperm may still be altered (66; 67). In the following sections, we explore evidence of transgenerational transmission through the three classes of epigenetic marks in sperm cells, examining their regulation through spermatogenesis and highlighting potential consequences on offspring reprogramming.…”
Section: Epigenetic Signatures Of Stress Experiencementioning
confidence: 99%
“…Gestational or early life exposures likely reprogram primordial germ cells in the embryonic gonadal ridge or immature postnatal testis, and insults later in life may instead impact germ cells further along in spermatogenesis (64). Once sperm are fully mature, they are stored in the epididymis where epigenetic marks are thought to be largely impervious to change or to the environment (65), although limited evidence of intercellular communication between mature sperm and the epididymal epithelial cells suggests that small noncoding RNA populations in mature sperm may still be altered (66; 67). In the following sections, we explore evidence of transgenerational transmission through the three classes of epigenetic marks in sperm cells, examining their regulation through spermatogenesis and highlighting potential consequences on offspring reprogramming.…”
Section: Epigenetic Signatures Of Stress Experiencementioning
confidence: 99%
“…12 In the past 3 decades it has been shown that small membranous vesicles secreted by epididymal epithelial cells, i.e., epididymosomes, are involved in this sperm maturation. [13][14][15] Interestingly these epididymosomes have also been shown to transfer a specific sperm binding protein (ELSPBP1) to dead sperm during transit. 16 Recently, it was suggested that the cytoplasmic droplets, which are small cytoplasmic residues attached to the sperm after their release fromthe germinal epithelium and which migrates caudally along the sperm during epididymal transit, 13 represent a transient organelle that serves as an energy source essential for epididymal sperm maturation.…”
Section: Structure and Function Of The Epididymismentioning
confidence: 99%
“…This environment is, in turn, created by the combined secretory and absorptive of the lining epithelium and characterised by considerable segment-segment variation4. A central component of epididymal soma-spermatozoa intercellular communication are epididymosomes, a heterogeneous population of small membrane bound vesicles that are released from the epididymal epithelium via an apocrine secretory mechanism5678. Similar to the exosome population documented in other somatic tissues and bodily fluids, epididymosomes are able to relay a complex macromolecular cargo to recipient cells91011.…”
mentioning
confidence: 99%